Assessing acrylamide content in sterilized Californian-style black table olives using HPLC-MS-QQQ and a potentiometric electronic tongue - Martín-Vertedor, Daniel (2020)
The study aimed to evaluate the effects of olive cultivar (cvs. Manzanilla Cacereña and Hojiblanca) and the sterilization intensity/time-period (F0 of 1025minat 121±3°C) on the formation of acrylamide in table olives and brine. Olive cultivar and thermal sterilization had a significant impact on the amount of acrylamide produced (varying from 228±94 to 286±110 and 336±126 to 373±159ngg1, for table olives and brine, respectively, determined by HPLC-MS-QQQ). Moreover, for both cultivars, linear positive relationships (0.931R20.994) were found between the acrylamide concentration in olives and respective brine solutions, allowing to foresee a non-destructive indirect methodology for quantifying acrylamide in table olives. Finally, a potentiometric E-tongue was used to quantify acrylamide in both matrices. The lipid sensor membranes comprised on the sensor device showed potentiometric semi-logarithmic responses (0.962R20.999) towards the acrylamide concentration for aqueous standard solutions, permitting the establishment of accurate multiple linear predictive models for the quantification of acrylamide in olives and brine solutions (repeated K-fold-CV: 0.97±0.03R20.99±0.01; 12±8RMSE 28±14ngg1) for both olive cultivars. E-tongue could be used as non-destructive indirect detection method of acrylamide, based on the brine solution evaluation, and so, a complementary analytical tool to the conventional chromatographic analysis.